Rice transcription factor MADS32 regulates floral patterning through interactions with multiple floral homeotic genes. (18th December 2020) - Hu, Yun; Wang, Li; Jia, Ru; Liang, Wanqi; Zhang, Xuelian; Xu, Jie; Chen, Xiaofei; Lu, Dan; Chen, Mingjiao; Luo, Zhijing; Xie, Jiayang; Cao, Liming; et al.
Abstract : OsMADS32, an orphan gene and absent in eudicots, specifies rice floral patterning by interacting physically and genetically with multiple floral homeotic genes. Abstract: Floral patterning is regulated by intricate networks of floral identity genes. The peculiar MADS32 subfamily genes, absent in eudicots but prevalent in monocots, control floral organ identity. However, how the MADS32 family genes interact with other floral homeotic genes during flower development is mostly unknown. We show here that the rice homeotic transcription factor OsMADS32 regulates floral patterning by interacting synergistically with E class protein OsMADS6 in a dosage-dependent manner. Furthermore, our results indicate important roles for OsMADS32 in defining stamen, pistil, and ovule development through physical and genetic interactions with OsMADS1, OsMADS58, and OsMADS13, and in specifying floral meristem identity with OsMADS6, OsMADS3, and OsMADS58, respectively. Our findings suggest that OsMADS32 is an important factor for floral meristem identity maintenance and that it integrates the action of other MADS-box homeotic proteins to sustain floral organ specification and development in rice. Given that OsMADS32 is an orphan gene and absent in eudicots, our data substantially expand our understanding of flower development in plants.